Endogenous oxidative stress, but not ER stress, induces hypoxia‐independent VEGF120 release through PI3K‐dependent pathways in 3T3‐L1 adipocytes. (13th May 2013) - Takahashi, Kazuto; Miyokawa‐Gorin, Kaoru; Handa, Keiko; Kitahara, Atsuko; Moriya, Rie; Onuma, Hirohisa; Sumitani, Yoshikazu; Tanaka, Toshiaki; Katsuta, Hidenori; Nishida, Susumu; Yoshimoto, Katsuhiko; Ohno, Hideki; et al.
Abstract : Objective: Expressions of vascular endothelial growth factor (VEGF) are increased in obese adipocytes and is secreted from obese adipose tissue through hypoxia‐independent pathways. Therefore, we investigated the hypoxia‐independent mechanism underlying increased expression and release of VEGF in obese adipocytes. Design and Methods: We compared signal transduction pathways regulating VEGF with those regulating monocyte chemoattractant protein‐1 (MCP‐1), which is increased in obese adipocytes, in an in vitro model of artificially hypertrophied 3T3‐L1 adipocytes preloaded with palmitate, without the influence of hypoxia. Results: Palmitate‐preloaded cells exhibited significantly enhanced oxidative stress ( P < 0.01) and showed increased VEGF120 and MCP‐1 release ( P < 0.01, respectively), while endoplasmic reticulum (ER) stress was not induced. Increased VEGF120 release was significantly decreased with PI3K inhibitor LY294002 ( P < 0.01). In addition, antioxidant N‐acetyl‐cysteine (NAC) markedly diminished not only VEGF120 secretion ( P < 0.01) but also augmented Akt phosphorylation on Ser473 ( P < 0.01). In contrast, increased MCP‐1 release was suppressed with JNK inhibitor SP600125 and p38 MAPK inhibitor SB203580 ( P < 0.01). Conclusions: VEGF120 release from hypertrophied adipocytes can be enhanced through PI3K pathways activated by oxidative stress but not by ER stress, suggesting that VEGF120 secretion is regulated through oxidative stress‐dependent pathways distinct from those involved in MCP‐1 release through either JNK or p38 MAPK activation.